Upaya Meminimalisir Tingkat Glossophobia Melalui Konseling Kelompok Teknik Assertive Training Pada Siswa Kelas X SMAS Katolik Budi Murni 3 Medan - Cristin Mutiara Damanik; Abdul Murad (INDONESIAN COUNSELING AND PSYCHOLOGY, 2023)
There were students in class X SMAS Catholic Budi Murni 3 Medan. When the group assignments consisted of 5 people in 1 group, almost every group there were students who did not participate actively, avoided or chose to remain silent. This study aims to minimize the level of glossophobia through group counseling with Assertive Training techniques for class X students at SMAS Catholic Budi Murni 3 Medan. The type of research used is counseling guidance action research (PTBK). The population determined was class X students and the sampling technique in this study used purposive sampling. Based on the sampling technique, 8 students were determined as research subjects. The data collection tool used is the glossophobia scale, the results of the instrument validity test are 31 valid items from 40 items, and the instrument reliability is 0.893. The results showed that the level of glossophobia before being given group counseling services with assertive training techniques had an average score of 74.7%, after being given services the average score was 51,6% in the first cycle and the second cycle the average score was 40,7%. The conclusion of the study was that 87.5% of students experienced an increase in scores, namely being in the low category, so this research was successful and was carried out in only 2 cycles. It can be concluded that group counseling with assertive training techniques can minimize the level of glossophobia in class X students of SMAS Catholic Budi Murni 3 Medan.